Spectroelectrochemical study of picolinic acid adsorption during silver electrodeposition - Vazquez, Cecilia Irene (2015)
The adsorption of picolinic acid (PA) onto HOPG electrodes during silver electrodeposition at pH 3.0 was examined using conventional electrochemical techniques: cyclic voltammetry and impedance measurements (differential capacity-potential plots) and Surface-Enhanced Raman Spectroscopy (SERS), through a wide range of electrode potentials. The spectroelectrochemical results indicate that the electroactive species for silver electrodeposition are Ag+ ions and [Ag(Pic)] complexes, in spite of the predominant species in solution being the zwitterion (HPic). Adsorption of the anion (Pic-) occurs through a wide potential range where the electrode surface charge density is positive. However, HPic deprotonation, hydrogen formation and Pic- desorption, with the consequent decrease in SERS intensity, occur at the zero-charge potential (pzc) for HOPG.